The Effect of Consumer Satisfaction and Brand Image on Repurchase Intention with Customer Loyalty as a Mediating Variable - Nirwandi Nirwandi; Darmianti Razak; Muzdalifah Muhammadun; Ahmad Dzul Ilmi Syarifuddin; Arwin Arwin (Jurnal Ekonomi, Manajemen, dan Bisnis, 2026)
The present study is conducted to scrutinize the degree to which consumer satisfaction and brand image serve as antecedents of repurchase intention, while positioning customer loyalty as an intervening variable within the purchasing behavioral context of Celcius Parepare Branch consumers. A quantitative associative framework was applied as the methodological backbone of this investigation, wherein data were systematically drawn from 140 participants determined through purposive sampling. All collected data were subsequently processed and evaluated through the Partial Least Squares Structural Equation Modeling (PLS-SEM) analytical technique, operated via SmartPLS 4 software. Empirical results demonstrate that both consumer satisfaction and brand image yield constructive and statistically meaningful direct effects on consumers repurchase intention. Furthermore, consumer satisfaction proves to be a robust predictor of customer loyalty, whereas brand image contributes only marginally to loyalty development. Customer loyalty itself emerges as a consequential driver of repurchase intention, reinforcing its structural relevance within the model. The mediation assessment further discloses that customer loyalty operates as a significant conduit through which consumer satisfaction indirectly shapes repurchase intention, yet this intermediary function is rendered statistically negligible when brand image is positioned as the antecedent variable. Taken together, these outcomes highlight that cultivating consumer satisfaction stands as the most impactful strategic imperative for concurrently reinforcing loyalty and strengthening repurchase intention, while brand image predominantly channels its effect through a direct route rather than through loyalty as a mediating pathway.